Women: the key to food security [in Japanese] - Quisumbing, Agnes R.; Brown, Lynn R.; Feldstein, Hilary Sims; Haddad, Lawrence James; Peña, Christine (International Food Policy Research Institute, 1997)
This food policy report synthesizes current research about the roles that women play in ensuring food security in the developing world--P. v.